2021
DOI: 10.1016/j.biopsych.2020.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Corticostriatal Circuit Activity Improves Cognitive Flexibility and Prevents Body Weight Loss in Activity-Based Anorexia in Rats

Abstract: BackgroundThe ability to adapt behavior to changing environmental circumstances, or cognitive flexibility, is impaired in multiple psychiatric conditions, including anorexia nervosa (AN). Exaggerated prefrontal cortical activity likely underpins the inflexible thinking and rigid behaviors exhibited by patients with AN. A better understanding of the neural basis of cognitive flexibility is necessary to enable treatment approaches that may target impaired executive control. MethodsUtilizing the activity-based an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 63 publications
8
33
1
Order By: Relevance
“…This may lead to an activation of the frontostriatal brain circuitry, potentially contributing to habit formation [ 27 ]. Consistent with that notion is a recent study using an animal model for AN that found that suppression of corticostriatal connections improved cognitive flexibility and was associated with less weight loss, suggesting that reducing higher-order cortical input to the subcortical reward circuitry might be beneficial to treat AN, by reducing cognitive rigidity and anxiety [ 41 ].…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…This may lead to an activation of the frontostriatal brain circuitry, potentially contributing to habit formation [ 27 ]. Consistent with that notion is a recent study using an animal model for AN that found that suppression of corticostriatal connections improved cognitive flexibility and was associated with less weight loss, suggesting that reducing higher-order cortical input to the subcortical reward circuitry might be beneficial to treat AN, by reducing cognitive rigidity and anxiety [ 41 ].…”
Section: Resultsmentioning
confidence: 70%
“…A biological approach could apply in humans where “turning off” of frontal input was able to improve survival in the ABA model [ 41 ]. In fact, a recent pilot study in AN using repetitive transcranial magnetic stimulation found less over-control for food choices, suggesting more cognitive flexibility [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have emphasized the behavioral complexities of ABA, and more recent reports have begun to unravel the neurobiology potentially underlying ABA 34,42,[45][46][47]56,57 . Despite these advances, no study to date has identified a neural circuit capable of combating ABA development and/or progression by addressing both anorexia and hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the mPFC-LH circuit may play important and underappreciated roles in the pathogenesis of psychometabolic conditions at opposite ends of the body weight sprectrum. For example, excessive cognitive control related to increased mPFC activity is associated with anorexia nervosa 11 and excessive dietary self control 6 , while chronic inhibiton of the mPFC reduces anorectic symptoms in a rat model of activity-based anorexia 70 . On the other hand, decreased activity upon consumption removes this restraint and may, in some circumstances, promote body weight gain.…”
Section: Discussionmentioning
confidence: 99%